MAPPING GLOBAL PASSPORT POWER : A K-MEANS CLUSTERING APPROACH TO ANALYZING STRENGTH AND DISPARITIES - Dewa Gede Raka Suputra; Komang Sudi Astrini; Komang Agus Anjas Putra; Maria Magdalena Indri; Mariana Klarita Daud; Putu Sugiartawan (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study examines global passport strength and its influence on international mobility. Using a dataset of 199 countries from Kaggle, the research applies K-Means Clustering to investigate the relationship between passport rankings and visa-free access. Results reveal Singapore as the global leader, with visa-free access to 195 destinations, while Bangladesh ranks lowest with access to only 40 destinations. A strong negative correlation (-0.99) between passport rankings and visa-free access highlights that greater visa-free access improves a country's passport ranking. Descriptive, comparative, and trend analyses illustrate disparities, with developed nations achieving higher mobility levels. The clustering analysis groups countries based on their visa-free access, identifying distinct patterns of global mobility. The findings emphasize the critical role of international agreements and diplomatic relations in enhancing passport strength and reducing mobility disparities. This study provides valuable insights into the factors shaping passport power, offering guidance for policies aimed at fostering equitable global mobility.